Operator algebras and applications. - Takesaki, Masamichi, 1933-; Evans, David E. (London Mathematical Society lecture note series ;, 1988)
These volumes form an authoritative statement of the current state of research in Operator Algebras. They consist of papers arising from a year-long symposium held at the University of Warwick. Contributors include many very well-known figures in the field.